A Cluster Analysis of Mutual Funds Data - Narabin, Santit; Boongasame, Laor (My University, 2018)
The factors of clustering mutual fund (such as Net Asset Value (NAV)) do not direct to both return and risk of mutual funds which they are important factors for investors. This research helps an investor can estimate profit and loss rate of the mutual fund in his/her portfolio by using the net asset value change ratios (NAVCR). Then, both the NAVCR and value of each mutual fund will be used for clustering. For building a portfolio, the mutual funds could be selected from the diversified groups in order to reduce risk. The mutual fund data at different times from the set for the fiscal year 2010 - 2017 are used. The results of our analysis show that our models offer significantly better performance than the portfolio management model derived from the random portfolio management.
Keywords: K-mean clustering; Net asset value change ratios; Portfolio; Risk, Return